1998
DOI: 10.1359/jbmr.1998.13.11.1747
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Established Postmenopausal Osteoporosis with Raloxifene: A Randomized Trial

Abstract: Raloxifene is a selective estrogen receptor modulator that in experimental animals acts as an estrogen receptor antagonist in breast and endometrium but as an estrogen receptor agonist in the skeletal and cardiovascular systems. We conducted a 1-year prospective, randomized, double-blind trial in 143 postmenopausal osteoporotic women (mean ؎ SD age, 68.4 ؎ 5.0 years) with at least one prevalent vertebral fractures and low bone mineral density (BMD), comparing groups receiving raloxifene at 60 mg/day (RLX60) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
13

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(99 citation statements)
references
References 31 publications
(27 reference statements)
5
81
0
13
Order By: Relevance
“…Other studies have reported a similar decrease in BTM in response to raloxifene for CTX measured using other methods [1,2,25] and for total PINP measured by a different autoanalyser method [26] . The changes in BTM occur earlier and are of a greater magnitude than the change in bone density.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Other studies have reported a similar decrease in BTM in response to raloxifene for CTX measured using other methods [1,2,25] and for total PINP measured by a different autoanalyser method [26] . The changes in BTM occur earlier and are of a greater magnitude than the change in bone density.…”
Section: Discussionsupporting
confidence: 58%
“…Raloxifene is a selective estrogen receptor modulator (SERM) that has beneficial effects on bone and lipids with no detrimental effects on the breast or endometrium [1,2] and is licensed for the treatment and prevention of osteoporosis [3] . Raloxifene treatment results in an increase in bone mineral density (BMD), reduction in bone turnover markers (BTM) and reduced risk of vertebral fractures [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Os moduladores de receptor de estrógeno de segunda geração como raloxifeno, não têm efeito agonista nos tecidos reprodutivos. Há vários trabalhos de uso clínico de raloxifeno 60 mg em osteoporose pós menopausa (1,2). Há um estudo do efeito de raloxifeno sobre a incidência de fraturas, mostrando redução de fraturas vertebrais em radiografia em 50% no período de 24 meses; o estudo continua para avaliação de 36 meses (3).…”
Section: Moduladores De Receptor De Estrógenounclassified
“…O clomifeno já está em uso clínico há vários anos para tratamento de infertilidade feminina, enquanto droloxifeno, idoxifeno e toremifeno ainda estão em fase II/III de pesquisas clínicas. A estrutura do raloxifeno está representada na figura l. A parte inferior da estrutura do raloxifeno liga-se ao receptor de estrógeno, enquanto a cadeia lateral básica se liga à um sítio diferente e leva às propriedades antagonistas do composto (8,9).…”
Section: Estrutura Químicaunclassified
“…Porém, raloxifeno não causa estimulação endometrial (tabela 1). Em estudos clínicos recentes, raloxifeno mostrou efeitos benéficos no esqueleto (8,9), o que levou à aprovação do raloxifeno para a prevenção e tratamento de osteoporose no Brasil. Nesta revisão, abordaremos aspectos pré-clínicos/clínicos gerais atuais do raloxifeno e suas perspectivas para o futuro.…”
unclassified